Impact of winter monsoon circulations on aerosol optical depth in Bac Lieu and Bac Giang - Thành, Phạm Xuân; Anh, Nguyễn Xuân; Thúy, Đỗ Ngọc; Huy, Lê Việt (Vietnam Journal of Earth Sciences, 2012)
Impact of winter monsoon circulations on aerosol optical depth (AOD) in Bac Giang and Bac Lieu stations are analyzed through the wind speed data series of the National Center for Environmental Prediction/Department of Energy (NCEP/DOE-2) and the AOD data obtained from AERONET stations network (AErosol RObotic NETwork) of the National Aeronautic and Space Administration (NASA) in Bac Giang and Bac Lieu. To accomplish this, first we defined the rules change over time of AOD at Bac Giang and Bac Lieu stations. The correlation between AOD at Bac Lieu station with wind speed of Asia, and the relationship between the rules of variation of AOD at Bac Giang station and the winter monsoon are determined. The results show that the value of AOD at Bac Lieu in the middle of winter (December, January and February) is the highest while the value of AOD at Bac Giang in the early winter (October) and the last winter (February, March) is the highest. The correlation between wind speed in the middle of winter from AOD at Bac Lieu and from southeastern China and northern Vietnam has the highest value (from +0.4 to +0.5). This result shows the affect of East Asia winter monsoon to the AOD at Bac Lieu. On the basis of analysis of wind speed on the surface and on the high levels for period of early winter and last winter showed the circulation period for accumulation of aerosol particles high AOD value at Bac Giang station.